2014
DOI: 10.4236/psych.2014.511146
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Awareness and Acceptance of Disability in Mexican Mothers of Autistic Children

Abstract: The arrival of a disabled child is overwhelming to any family; it is often a shocking event that impacts the life cycle of the family. Several studies highlight the support that must be provided to parents of children with disabilities. In Mexico, this support is not often promoted in a successfully way neither in official nor private institutions. The purpose of this study was to assess the effect of a special assistance program carried out with five autistic children' mothers, aged between 28 and 43 years (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Care of children with disabilities is often provided by the family (Duran, Cottone, Ruzek, Mashburn, & Grissmer, 2018; Fernández, Enriquez, Huerta, & Castellanos, 2016; Flóres-Torres, Montalvo-Prieto, Herrera-Lian, & Romero-Massa, 2010; Guevara-Benites & González-Soto, 2012). In Mexican families, results of studies (Fernández, Enriquez, Huerta, et al, 2016; Rea-Amaya & Acle-Tomasini, 2014) have shown that mothers are likely the caregivers who provide physical and emotional support toward the children with developmental disability. The mothers are often responsible for providing personal hygiene and administering and monitoring medical treatments (Amaya & Tomasini, 2014; Crettenden, Wright, & Skinner, 2013; Deater-Deckard, Li, & Bell, 2015; Fávero-Nunes & dos Santos, 2010; Marre, Monnet, & San Román, 2015; Munsell, Kilmer, Cook, & Reeve, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Care of children with disabilities is often provided by the family (Duran, Cottone, Ruzek, Mashburn, & Grissmer, 2018; Fernández, Enriquez, Huerta, & Castellanos, 2016; Flóres-Torres, Montalvo-Prieto, Herrera-Lian, & Romero-Massa, 2010; Guevara-Benites & González-Soto, 2012). In Mexican families, results of studies (Fernández, Enriquez, Huerta, et al, 2016; Rea-Amaya & Acle-Tomasini, 2014) have shown that mothers are likely the caregivers who provide physical and emotional support toward the children with developmental disability. The mothers are often responsible for providing personal hygiene and administering and monitoring medical treatments (Amaya & Tomasini, 2014; Crettenden, Wright, & Skinner, 2013; Deater-Deckard, Li, & Bell, 2015; Fávero-Nunes & dos Santos, 2010; Marre, Monnet, & San Román, 2015; Munsell, Kilmer, Cook, & Reeve, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Mexican families, results of studies (Fernández, Enriquez, Huerta, et al, 2016; Rea-Amaya & Acle-Tomasini, 2014) have shown that mothers are likely the caregivers who provide physical and emotional support toward the children with developmental disability. The mothers are often responsible for providing personal hygiene and administering and monitoring medical treatments (Amaya & Tomasini, 2014; Crettenden, Wright, & Skinner, 2013; Deater-Deckard, Li, & Bell, 2015; Fávero-Nunes & dos Santos, 2010; Marre, Monnet, & San Román, 2015; Munsell, Kilmer, Cook, & Reeve, 2012). Caregiving is done in addition to other responsibilities that mothers have for the rest of the family.…”
Section: Introductionmentioning
confidence: 99%